Vestibular and Ocular Motor Properties in Lateral Medullary Stroke Critically Depend on the Level of the Medullary Lesion - Lee, Seung-Han; Kim, Jae-Myung; Schuknecht, Bernhard; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2020)
Background: Lateral medullary stroke (LMS) results in a characteristic pattern of brainstem signs including ocular motor and vestibular deficits. Thus, an impaired angular vestibulo-ocular reflex (aVOR) may be found if the vestibular nuclei are affected. Objective: We aimed to characterize the frequency and pattern of vestibular and ocular-motor deficits in patients with LMS. Methods: Patients with MR-confirmed acute/subacute unilateral LMS from a stroke-registry were included and a bedside neuro-otological examination was performed. Video-oculography and video-head-impulse testing (vHIT) was obtained and semicircular-canal function was determined. The lesion location/extension as seen on MRI was rated and involvement of the vestibular nuclei was judged. Results: 17 patients with LMS (age=59.4±14.3y) were included. All patients had positive H.I.N.T.S. vHIT showed mild-to-moderate aVOR-impairments in three patients (ipsilesional=1; ipsilesional and contralesional=1; contralesional=1). Spontaneous nystagmus (n=10/15 patients) was more often beating contralesionally than ipsilesionally (6 vs. 3) and was accompanied by upbeat-nystagmus in four patients. Head-shaking nystagmus was noted in seven subjects, ipsilesionally-beating in six and down-beating in one. On brain MRI, damage of the most caudal parts of the medial and/or inferior vestibular nucleus was noted in 13 patients. Only those two patients with lesions affecting the rostral medulla oblongata demonstrated an ipsilaterally-impaired aVOR. Conclusions: While subtle ocular motor signs pointed to damage of the central-vestibular pathways in all 17 patients, aVOR-deficits were infrequent, restricted to those patients with rostral medullary lesions and if present mild-to-moderate only. This can be explained by lesions located too far caudally and too far ventrally to substantially affect the vestibular nuclei.